Finding the Fertile Phase: Low-Cost Luteinizing Hormone Sticks Versus Electronic Fertility Monitor. Issue 3 (May 2018) - Barron, Mary Lee; Vanderkolk, Kaitlin; Raviele, Kathleen
Abstract: Purpose: To investigate if generic Wondfo ovulation sticks (WLH) are sufficiently sensitive to the luteinizing hormone (LH) surge in urine when used with the Marquette Fertility Algorithm. The electronic hormonal fertility monitor (EHFM) is highly accurate in detecting the LH surge but cost of the monitor and the accompanying test sticks has increased over the last several years. The EHFM is sensitive to detect the LH surge at 20 milli-international units per milliliter (mIU/mL); the WLH sticks are slightly less sensitive at 25 mIU/mL. Study Design and Methods: A convenience sample of women using the Marquette Method of Natural Family Planning with the EHFM to avoid pregnancy were recruited ( N = 54). Each participant used the EHFM every morning after cycle day 6 and tested morning and evening urine with the WLH stick until the day following detection of the LH surge on the EHFM. Results: Forty-two women provided 219 cycles. Frequency of LH surge detection was 182/219 (83.1%) for EHFM and 203/219 (92.7%) for WLH sticks. Agreement between the EHFM and the WLH on the day of the LH surge was 97.7%. High fertility readings providing a warning of peak fertility at least 5 days before peak was 67% for the WLH; the EHFM was 47.7%. Paired sample correlations for high fertility was .174 ( p = .014) and paired sample differences t was -4.729 ( p = .000). Clinical Implications: The WLH stick is sufficiently sensitive to use in place of the EFHM for determining peak fertility and with the Marquette Fertility algorithm. Even with minimal use, WLH sticks cost about half the price of the monitor strips and provide more flexibility of use. Cost differences increase with the number of sticks used per cycle. Further research with a larger sample is needed to verify results. Abstract : This study compared two methods of detection of the fertile window among women who were using the Marquette Method of natural family planning. The ovulation sticks, which were one-half of the costs of the electronic hormonal fertility monitor strips, were found to be sufficiently sensitive for determining peak fertility when used with the Marquette Fertility algorithm. These data can be helpful for couples in making choices as the fertility strips and sticks are not usually covered by health insurance.